2011
DOI: 10.1074/jbc.m110.176305
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin and Neuroligins Cooperate to Regulate Synapse Formation in Hippocampal Cultures

Abstract: Cadherins and neuroligins (NLs) represent two families of cell adhesion proteins that are essential for the establishment of synaptic connections in vitro; however, it remains unclear whether these proteins act in concert to regulate synapse density. Using a combination of overexpression and knockdown analyses in primary hippocampal neurons, we demonstrate that NL1 and N-cadherin promote the formation of glutamatergic synapses through a common functional pathway. Analysis of the spatial relationship between N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 34 publications
(49 reference statements)
1
52
0
Order By: Relevance
“…Our results are in agreement with a previous report in which suppression of N-cad function by overexpression of a dominant-negative mutant was shown to impair presynaptic organization and synapse number (Togashi et al, 2002;Vitureira et al, 2012). Furthermore, Aiga et al (2011) have recently shown that synapse density increases following N-cad overexpression (Aiga et al, 2011) only in young neurons. The discrepancy between our study and those that show no effect on synapse number after N-cad overexpression (Okamura et al, 2004;Vitureira et al, 2012) could be attributed to the superior transfection rate (Ͼ60%) in the current study, Figure 8.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in agreement with a previous report in which suppression of N-cad function by overexpression of a dominant-negative mutant was shown to impair presynaptic organization and synapse number (Togashi et al, 2002;Vitureira et al, 2012). Furthermore, Aiga et al (2011) have recently shown that synapse density increases following N-cad overexpression (Aiga et al, 2011) only in young neurons. The discrepancy between our study and those that show no effect on synapse number after N-cad overexpression (Okamura et al, 2004;Vitureira et al, 2012) could be attributed to the superior transfection rate (Ͼ60%) in the current study, Figure 8.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, in the rat RT4-D6P2T schwannoma cell line, UTP induces a transient elevation in concentrations of intracellular Ca 2+ and a subsequent cytoskeletal reorganisation [32]. In this context, N-cadherin, a member of the Ca 2+ -dependent CAM family, is related to multiple cytoskeletal elements and has an important role in SC migration, neurite outgrowth, synaptic rearrangement, creation of SC-SC junctions, and the alignment of SCs with axons [4,5,[33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The 488-kb gain in CN encompasses CDH2, encoding N-cadherin, which is expressed in brain, skeletal and cardiac muscles and has critical roles in synaptic adhesion, dendritic morphology and neuritic growth. [55][56][57][58][59] CDH2 has been extensively studied in AD. For example, inhibition of N-cadherin function has been reported to accelerate Ab-triggered synapse damage.…”
Section: Rare Autosomal Cnvs In Eo-fad Bv Hooli Et Almentioning
confidence: 99%